2017
DOI: 10.3141/2663-17
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and Modeling Drivers’ Deceleration Behavior from Normal Driving

Abstract: Most research in vehicle automation has mainly focused on the safety aspect with only limited studies on occupants' discomfort. In order to facilitate their rapid uptake and penetration, autonomous vehicles (AVs) should ensure that occupants are both safe and comfortable. Recent research however revealed that people felt uncomfortable when AVs braked. This may be due to their robot-like braking performance. Existing studies on drivers' braking behaviour investigated data either from controlled experiments or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…In the yielding conditions, it came to a full stop at 5 m before the pedestrian. The three different yielding behaviors exhibited different braking characteristics: Gentle braking: At a distance of 45 m away from the pedestrian, the car started to brake steadily, to indicate a deliberate but smooth yielding behavior, resulting in a total braking distance of 40 m. This was done to emulate a deceleration rate of 2.4 m/s 2 which was found as the deceleration rate for average and common braking by previous research [5]. This condition was therefore treated as a representative of a 'normal' braking pattern which would ideally correspond with a 'yielding' message from an eHMI.…”
Section: Apparatus and Study Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In the yielding conditions, it came to a full stop at 5 m before the pedestrian. The three different yielding behaviors exhibited different braking characteristics: Gentle braking: At a distance of 45 m away from the pedestrian, the car started to brake steadily, to indicate a deliberate but smooth yielding behavior, resulting in a total braking distance of 40 m. This was done to emulate a deceleration rate of 2.4 m/s 2 which was found as the deceleration rate for average and common braking by previous research [5]. This condition was therefore treated as a representative of a 'normal' braking pattern which would ideally correspond with a 'yielding' message from an eHMI.…”
Section: Apparatus and Study Setupmentioning
confidence: 99%
“…Aggressive braking: At a distance of 24 m away from the pedestrian, the car braked hard. In this aggressive yielding behavior, the total braking distance was 19 m. This was done to emulate a deceleration rate of 5.17 m/s 2 which was found as the maximum deceleration rate for hard braking by previous research [5]. This condition was therefore treated as a representative of behavior that would initially seem to contradict a 'yielding' message from an eHMI.…”
Section: Apparatus and Study Setupmentioning
confidence: 99%
“…On the other hand, there might be variation between lead gaps from different lane change motivations and/or different road types, i.e., between-cluster variation. Therefore, a statistical model is needed to jointly control both within-and betweencluster variations(Deligianni et al, 2017).…”
mentioning
confidence: 99%
“…Additionally, a study project conducted among Pan-Europeans found that behaviour of drivers, specifically deceleration, was mainly due to detecting danger on the road followed by hard braking that resulted in slowing of the vehicle (31). Thus, anxiety and stress play a major role defining the behaviour of drivers while driving.…”
Section: Discussionmentioning
confidence: 99%